The number of obstructive colorectal cancers in Japan has increased during the COVID-19 pandemic: A retrospective single-center cohort study. (December 2020) - Mizuno, Rei; Ganeko, Riki; Takeuchi, Go; Mimura, Kazuya; Nakahara, Hideto; Hashimoto, Kyoichi; Hinami, Junsuke; Shimomatsuya, Takumi; Kubota, Yoshihiro
Abstract: Background: The global pandemic of COVID-19 has changed cancer treatment environments. In Japan, cancer screenings were halted and the numbers of endoscopies and surgeries were restricted in some hospitals based on the state of emergency declared. Herein, we investigated the impact of the COVID-19 pandemic on the characteristics of colorectal cancer (CRC) patients in facilities that are on the frontline of both COVID-19 and cancer treatments. Patients and methods: We retrospectively analyzed the cases of all of the CRC patients (n = 123) who underwent surgery at our regional cancer treatment center and tertiary emergency hospital in Japan during a 120-day period ranging from before to after the state of emergency declaration. CRC patients during the corresponding period in the previous year were also examined. Results: Although the number of CRC patients did not show a significant change related to the pandemic, the incidence of obstructive CRCs significantly increased after the pandemic's start. The numbers of outpatients and colonoscopies both decreased, which could have resulted in the decrease of CRC patients detected by cancer screening during the pandemic. The numbers of symptomatic CRC patients and emergency admissions both increased significantly during the pandemic. Conclusion: Our findings indicate the possibility that the discovery of CRCs in patients could be delayed due to the halt in screenings caused by the COVID-19 pandemic, resulting in the increase of obstructive CRCs. These results highlight the importance of cancer screening and suggest that the screening system for cancers should be reorganized before future pandemics. Highlights: The proportion of obstructive CRC patients increased during the COVID-19 pandemic. During the COVID-19 pandemic, CRC patients were mainly detected by abdominal symptoms but not by cancer screening. It is possible that the delays in the detection and surgeries due to halted screenings promoted the CRC progression. The screening systems for cancer should be reorganize before a future pandemic of unknown infectious disease.